Divergent regulation of cellular cholesterol metabolism by seaweed-derived fucosterol and saringosterol - Zhan, Na; Martens, Nikita; Li, Yanlin; Voortman, Gardi; Leijten, Frank; Friedrichs, Silvia; Caspers, Martien P. M.; Verschuren, Lars; Vanmierlo, Tim; Smit, Marieke; Kuipers, Folkert; Jonker, Johan W.; et al. (Frontiers in Marine Science, 2025)
Marine sterols from brown seaweeds, particularly fucosterol and its oxidized derivative saringosterol, have shown therapeutic potential for Alzheimer’s disease (AD) and cardiovascular diseases. Here, we aimed to elucidate the cellular and in vivo mechanisms underlying their beneficial effects. In human HepG2 hepatocytes and CCF-STTG1 astrocytoma cells, we assessed liver x receptor (LXRα /LXRβ) activation, sterol uptake, and effects on cholesterol metabolism using luciferase reporter assays, GC–MS sterol profiling, and 13C-acetate incorporation. In THP-1–derived macrophages, we evaluated sterol-induced cholesterol efflux using radiolabeled [3H]-cholesterol assays and characterized anti-inflammatory responses by quantifying lipopolysaccharide (LPS) -induced cytokine production. Wild-type C57BL/6J mice were fed diets enriched with either fucosterol (0.2% w/w) or saringosterol (0.02% w/w) for 7 days, after which sterol profiles in serum, liver, and brain were quantified by GC–MS. Hippocampal transcriptional responses were assessed by RNA sequencing. Both fucosterol and saringosterol were internalized by HepG2 and CCF-STTG1 cells and activated LXRα/β, but elicited distinct metabolic effects: fucosterol increased cholesterol synthesis and intracellular desmosterol, whereas saringosterol reduced both; only saringosterol suppressed LPS-induced interleukin (IL)-6 and tumor necrosis factor (TNF)-α production in macrophages, while both enhanced cholesterol efflux. In vivo, fucosterol somewhat elevated hepatic desmosterol and decreased 5α-cholestanol and circulating oxysterols, whereas saringosterol also increased hepatic desmosterol and elevated 7α-hydroxycholesterol in liver and brain as well as serum 27-hydroxycholesterol. Transcriptome analysis revealed that fucosterol primarily modulated synaptic signaling and hormonal pathways linked to neuronal plasticity, while saringosterol affected protein quality control and neurodegenerative pathways. These data are the first on the direct comparison of the cellular and in vivo effects of fucosterol and saringosterol, revealing shared LXR activation but divergent impacts on hepatic, brain and systemic cholesterol metabolism and expression of genes involved in neural pathways, indicating complementary neuroprotective effects with therapeutic potential for AD and related disorders.